Introduction to biotechnologies and biomimetics for civil engineering - Pacheco-Torgal, F. (2015)
This chapter starts with an overview on the sustainable development crucial challenges. The ones directly or indirectly related to the field of civil engineering are highlighted. These include greenhouse gas emissions (GHG) related to the energy consumption of the built environment, aggravated by urbanization forecast expansion, and the recent increase in building cooling needs due to climate change. It also includes the depletion of nonrenewable raw materials and mining-related environmental risks in terms of biodiversity conservation, air pollution, and contamination of water reserves. Some shortcomings of engineering curriculum to address sustainable development challenges (especially civil engineering) are described. Possible contributions of biotechnologies and biomimetics to sustainable development and the rebirth of civil engineering curriculum are suggested. A book outline is also presented.